Community managers, content curators, and other new professional profiles for the social Web - Sanz-Martos, Sandra (Anuario ThinkEPI, 2014)
The main professional profiles created within the social web are identified (such as the community manager and content curator), describing their main tasks, competencies, weight in organizations, and fit with the profile of information professionals.